MANAJEMEN KEGIATAN INTRAKURIKULER DAN EKSTRAKURIKULER BERBASIS INKLUSI DI SDN BETET 1 KOTA KEDIRI - Sri Wulandari; Maisyaroh Maisyaroh; Djum Djum Noor Benty; Sri Wulandari; Maisyaroh Maisyaroh (Universitas Negeri Malang, 2024)
Abstract: This study aims to determine, (1) planning of intra and extra activities; (2) organizing intra and extra activities; (3) intracuricular and extracurricular activities; (4) assessment of intra and extra activities; (5) supporting factors for intra and extra activities; 9intra and extra activity inhibiting factors; and (7) efforts to overcome the constraints of intra and extra activities. This research is SDN Betet 1 Kediri City. Data collection techniques through interviews, observation, and documentation. The analysis technique used is the reduction, data display, and data verification. The results of this study are, (1) planning for intra activitis beginning with the teacher preparing lesson plans, modified lesson plans and PPI for special classes, therapy programs, and compiling extracurricular programs; (2) organizing intra and extra activities namely the school principal issues a decree to regulate the work of teachers and staff of employees; (3) implementation of intra activities and that is by implementing lesson plans, implementing therapeutic programs, and implementing extracurricular programs; (4) assessment of intracuricular and extracurricular activities is written in the report cards of student, for students with special needs added reports of therapeutic activities; (5) supporting factors for intracuricular activities, namely human resources with various potentials, supporting facilities and community carrying capacity. Whereas extra activities namely adequate facilities, contributions form parents, and cooperation with outside parties; (6) the inhibiting factors of intra activities are limited budget and parents’ educational background. While the inhibiting factors of extra activities are limited budget and students who lack discipline; and (7) efforts to overcome barriers to intra activities, namely communication with parents. While efforts to overcome the constraints of extra activities are communication with parents and being more assertive to students..